Security Dilemma of the American Ballistic Missile Defense - Lukáš Kantor (Czech Journal of International Relations, 2013)
The article deals with the former US President Bush’s plan for the so-called third pillar of the American missile defense system in Poland and the Czech Republic in the context of American-Iranian and American-Russian relations. We assess the explanatory power of different but interconnected (neo)realist conceptualizations of security dilemma and deterrence. Specifically, the study evaluates the relative importance of classical security dilemma versus imperialist security dilemma and the explanatory power of three different modalities of deterrence. The paper further shows how Iran and Russia balanced the United States. We also argue that the American missile defense system was not primarily motivated by defensive realist worries about security, but rather by an offensive realist struggle for power and gains at the expense of others.